Oral presentation Urban green spaces, flora and fauna on the coast line. Sustainability issues - Vasquez Christodoulou, Marlen (My University, 2026)
Hadjikoumis A and Vasquez MI, Urban green spaces, flora and fauna on the coast line. Sustainability issues, Oral presentation, Sustainable Design in Coastal Areas (SUDESCO), Limassol, Cyprus, 22 July-3 August 2013.